A meta-synthesis of qualitative studies on cardiovascular disease patients’ experiences using digital health tools - Shao, Yuxuan; Hou, Xinyi; Peng, Qin; Hu, Mengdie; Li, Chaofeng (Frontiers in Public Health, 2025)
ObjectivesThis review aims to provide deeper insights into the patient experience by synthesizing qualitative findings from studies on DHTs used in CVD care. Specifically, it seeks to answer the question: What are the key barriers, facilitators, and trends in the use of digital interventions for CVD rehabilitation and self-management? Unlike traditional quantitative reviews, this study focuses on understanding the human factors, personal narratives, and contextual influences that shape the uptake and impact of DHTs in this area.MethodsA qualitative meta-synthesis was conducted on articles from the following major electronic databases: PubMed, Cochrane Library, CINAHL, Web of Science, Embase, PsycINFO, and Chinese databases, including Chinese National Knowledge Infrastructure (CNKI), Wanfang Database (CECDB), VIP Database, and China Biomedical Database (CBM). Studies published between 2020 and 2025 were included, and a systematic search was conducted using predefined keywords. Papers were selected based on predefined inclusion and exclusion criteria. The synthesis employed the aggregative integration approach from the meta-synthesis method proposed by the Joanna Briggs Institute (JBI) Evidence-based Healthcare Center in Australia. The extracted qualitative data were compared and analyzed in-depth.ResultsA total of 21 studies were included; 92 findings were extracted, organized into 13 categories, and consolidated into five synthesized findings: positive effects of DHTs; barriers to adoption and sustained use of DHTs; optimization needs and design priorities for DHTs; and culture- and disease-specific needs.ConclusionCardiovascular DHTs should be grounded in patients’ individualized needs and operationalized through age-friendly technological innovations, integration of professional support, and culturally sensitive design. Leveraging multiple pathways and modalities to strengthen the family–hospital–community support system will improve the acceptability of DHTs among people with cardiovascular disease. What this review uniquely adds is the patient-reported affective/relational value (e.g., feeling “continuously accompanied,” increased reassurance and trust through human-in-the-loop supervision) and the contextual value of digital health (age-friendly, culturally and disease-specific tailoring integrated with family/clinician support).